2014
DOI: 10.1016/j.ophtha.2013.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Health-Related Quality of Life and the Decision to Perform Surgery for Childhood Intermittent Exotropia

Abstract: Objective To assess associations between health-related quality of life (HRQOL) and the decision to perform strabismus surgery for children with intermittent exotropia (XT). Design Retrospective chart review Participants Children with intermittent XT Methods Included subjects, identified in a clinical practice, had assessment of HRQOL using the intermittent exotropia questionnaire (IXTQ), comprising Child, Proxy and Parent components (Parent domains: Function, Psychosocial, Surgery). IXTQ scores were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…We found a positive correlation between proxy and parent scores in our Asian population of patients with IXT, which agrees with the findings of a previous study on a western population 17. This indicates that the more worried the parents thought their child might be, the more worried the parents themselves were.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found a positive correlation between proxy and parent scores in our Asian population of patients with IXT, which agrees with the findings of a previous study on a western population 17. This indicates that the more worried the parents thought their child might be, the more worried the parents themselves were.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to our finding in the child IXT population, suggesting a lack of correlation in both adults and children. Indeed, studies have found that children with IXT rarely report HRQOL concerns,11 16 and this has led to the question of whether the IXTQ is insensitive to the concerns of children 17. However, as the child IXTQ was derived from interviews of children with IXT, these studies are likely confirmatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases reflected clinician and parental concern about possible worsening of the IXT, concerns which may have been influenced by knowledge of the treatment group and which are often key factors in the decision to proceed with IXT surgery. 33 In the fourth case, also in the observation group, a participant’s excellent stereoacuity did not support the diagnosis of constant exotropia.…”
Section: Discussionmentioning
confidence: 80%
“…In this way, the clinical ndings of IXT in these children do not fully correspond with their mental health. Another indication of this difference between the children and their parents were the ndings that parents with poorer HRQOL score were more likely to make the decision to perform surgery [11] . Chiu et al [12] have suggested that the HRQOL should be incorporated into the post-operative evaluation.…”
Section: Introductionmentioning
confidence: 99%